If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8y + -2(7x + -4y) = 0 4x + 8y + (7x * -2 + -4y * -2) = 0 4x + 8y + (-14x + 8y) = 0 Reorder the terms: 4x + -14x + 8y + 8y = 0 Combine like terms: 4x + -14x = -10x -10x + 8y + 8y = 0 Combine like terms: 8y + 8y = 16y -10x + 16y = 0 Solving -10x + 16y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16y' to each side of the equation. -10x + 16y + -16y = 0 + -16y Combine like terms: 16y + -16y = 0 -10x + 0 = 0 + -16y -10x = 0 + -16y Remove the zero: -10x = -16y Divide each side by '-10'. x = 1.6y Simplifying x = 1.6y
| 63+8(6x-1)=7(6x+1) | | -8(b-862)=-560 | | 16=8c | | 2.50(m+15.00)=662.5 | | 2.5r=95 | | 6(3x-6)=10x | | a+3ab+6+7a-2ab-1=0 | | 75+5x=10x+100 | | 9b-7b+6=-4b+78-3b | | 11x-160=56-7x | | 10+58=6x+2 | | 2x^4+3x-50=0 | | 5a+4b-5(7a-9b)= | | 26w+20=956 | | X-2x=125 | | (1+y)x^2-3yx+(1-y)=0 | | 2.50(m+15.00)=412.5 | | 84=2x-4+2x+4 | | 75=4529 | | -1-10r^2=-881 | | 3.4=y+2.1 | | -3x^2+8x-6=0 | | -8p-8=-14-7p | | -2x+(-21)=23 | | -1-10r^2=881 | | 84=4x^2-8+8-16 | | 929=97+13r | | 31/2(6x-21/2)+51/3=-62/3(-3x+16/5)+122/3 | | -70=-2(n+5)+7(4-6n) | | 21m-9= | | 15(b+17)=555 | | 7(f+37)=693 |